PENGARUH MOTIVASI KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN DAERAH KABUPATEN NIAS UTARA - Peringatan Harefa; Eliagus Telaumbanua (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to determine: a. to find out whether there is a partial effect of Work Motivation on the Performance of the Regional Personnel Agency of North Nias Regency. b. to find out whether there is a partial effect of Work Ability on the Performance of the Regional Personnel Agency of North Nias Regency. c. to find out how much influence Work Motivation and Work Ability simultaneously on the Performance of the Regional Personnel Agency of North Nias Regency.In this study the formulation of the problem "Is there an influence of work motivation and work ability on the performance of the Regional Personnel Agency of North Nias Regency?". The sample in this study was taken the entire population of 27 people, because of the limited population. The method used in this research is quantitative research method (Inferest), where the data collected is verified, validated, reliable and tested by the hypothesis using the t test and f test. At the 5% significance level, the results of the study found that: (1) Work motivation has a positive effect on the performance of the Personnel Board of North Nias Regency rcount>rtable (0.702>0.381), with the contribution of work motivation to employee performance of (rx1y) 0.702. (2) Work Ability has a positive effect on the performance of the Personnel Agency of North Nias Regency rcount>rtable (0.998>0.381), with the contribution of work ability to employee performance of (rx2y) 0.998.(3) Work Motivation and Work Ability have a positive effect on the performance of the Personnel Agency of North Nias Regency, which is shown from the results of the multiple linear regression test. Work motivation and work ability in explaining variations in performance variables is 55%, while the remaining 45% is explained by other variables outside the variables studied.